2013
DOI: 10.1039/c3ib20239a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the lateral diffusion of surface-anchored EGF demonstrates that receptor clustering modulates phosphorylation levels

Abstract: Upon activation, the epidermal growth factor (EGF) receptor becomes phosphorylated and triggers a vast signaling network that has profound effects on cell growth. The EGF receptor is observed to assemble into clusters after ligand binding and tyrosine kinase autophosphorylation, but the role of these assemblies in the receptor signaling pathway remains unclear. To address this question, we measured the phosphorylation of EGFR when the EGF ligand was anchored onto laterally mobile and immobile surfaces. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Numerous receptors, including EGFR (Stabley et al, 2013), integrins (Boettiger, 2012) toll-like receptor (Triantafilou et al, 2006), ErbB family (Yarden and Sliwkowski 2001) and Ephrin (Salaita et al, 2010) have been found to assemble into higher-order structures where downstream signaling events are often correlated to cluster formation. Consistent with our observations, a large heterogeneity in oligomer size has been reported for other RTKs, like the epidermal growth factor receptor (EGFR) (Abulrob et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous receptors, including EGFR (Stabley et al, 2013), integrins (Boettiger, 2012) toll-like receptor (Triantafilou et al, 2006), ErbB family (Yarden and Sliwkowski 2001) and Ephrin (Salaita et al, 2010) have been found to assemble into higher-order structures where downstream signaling events are often correlated to cluster formation. Consistent with our observations, a large heterogeneity in oligomer size has been reported for other RTKs, like the epidermal growth factor receptor (EGFR) (Abulrob et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our observations, a large heterogeneity in oligomer size has been reported for other RTKs, like the epidermal growth factor receptor (EGFR) (Abulrob et al, 2010). A recent study using a nano-patterned supported lipid bilayer technique to control EGFR clustering levels in living cells found that large-scale clustering of EGFR dampens its phosphorylation and that the cell endocytosis machinery contributes to this clustering behavior (Stabley et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…ECM stiffness is known to promote tumour progression by causing integrins to cluster within focal adhesions (Paszek et al, ; Levental et al, ), and direct interactions between these RTKs and integrins are thought to facilitate this localized enrichment (Wang et al, ; Sieg et al, ; Cabodi et al, ). This spatial clustering of RTK activity on stiff substrates alters the balance between ligand concentration and receptor auto‐phosphorylation, which ultimately amplifies ligand‐induced RTK signalling (Ichinose et al, ; Levental et al, ; Stabley et al, ). Additionally, the localization of RTKs within focal adhesions on stiff substrates promotes signalling through FAK, which increases cell migration (Sieg et al, ), while FAK is also required for RTK‐mediated oncogenic transformation (Benlimame et al, ).…”
Section: Potential Applications For Modelling Of Matrix Signallingmentioning
confidence: 99%
“…Cells treated with soluble EGF showed some areas of potential receptor clusters, while cells on immobilized EGF had large areas of dense EGFR signal (Figure a). Previous studies have defined receptor clusters as ranging from 0.07 to 3 μm 2 ; therefore, we classified any signal with an area less than 0.1 μm 2 as an isolated receptor and quantified the sizes of all clusters (Figure b). Few EGFR clusters were observed in cells in the bulk regardless of treatment condition (Supporting Information Figure 2); in addition, cells in the control condition had no observable receptor clusters at the wound edge.…”
Section: Resultsmentioning
confidence: 99%